Volume-weight Relation of Stacked Bamboo and Reed - Krishnankutty, C. N. (Indian Forester, 2003)
Volume-weight relations of stacked bamboo (Bambusa bambos) and reed (Ochlandra travancorica) were estimated for the first time, through field sampling in selected forest ranges in Kerala during the period February-March, 2000. Stacked volume refers to the volume of the stack closely packed with green poles (fresh utilisable portion of the culms immediately after felling) of bamboo or reed. Green weight refers to the weight of green bamboo or reed and ovendry weight refers to the weight in oven-dry condition. The estimated volume-weight relations are as follows: one cubic metre stacked green bamboo equals 0.268 tonne green weight (or 0.132 tonne oven-dry weight) and one cubic metre stacked green reed equals 0.207 tonne green weight (or 0.087 tonne oven-dry weight). The above figures are the multiplication factors for converting stacked volume (in vubic metre) to weight (in tonne). Therefore to convert a given volume (in cubic metre) of stacked green bamboo orreed to green or oven-dry weight (in tonne), the stacked volume has to be multiplied with the respective conversion factor.